Genetically modulated substrate reduction therapy - Coutinho, Maria Francisca (2018)
The concept of enzyme replacement as a potential therapeutic approach to ameliorate lysosomal storage disorders (LSDs) is virtually as old as the concept of LSD itself. In fact, right after the first enzymatic deficiency underlying a LSD was described, both concepts were established and, for years, enzyme replacement therapy (ERT) remained the golden standard for LSD treatment. Nevertheless, its ineffectiveness to correct brain pathology, together with its high cost and lifelong dependence are amongst the main reasons why additional therapeutic approaches are being (and have to be) investigated: chaperone therapy; gene enhancement and gene therapy. Still, no matter how effective the treatment or cutting-edge the technology used in any of these cases, the underlying rationale is virtually the same: an attempt to provide or enhance the activity of the missing enzyme. Yet, 20 years now, an alternative approach arose. Its theoretical basis were established in 1996, when Norman Radin came up with an academic prediction that Gaucher disease (GD) patients could also be treated with a drug able to slow the synthesis of glucosylceramide (GlcCer), the lipid that accumulates in this disorder. Unfortunately, the lack of suitable GD animal models made it difficult to adequately test his hypothesis by the time it was published. Still, the grounds were seeded for the appearance of a second line of work on the LSDs therapeutics field, whose aim was to prevent storage not by correcting the original enzymatic defect but, instead, by decreasing the biosynthesis of the substrate that is accumulated. This approach was called substrate reduction therapy (SRT) and will be the major focus of this talk. Special attention will be given to the most recent advances in the field, introducing the concept of genetic SRT (gSRT), which is based on the use of RNA-degrading technologies (RNA interference and single stranded antisense oligonucleotides) to efficiently promote substrate reduction by decreasing its synthesis rate. In summary, we will review and compare the results from different teams on the use of gene suppression technologies as tools to achieve substrate reduction.